Risk factors for obstetric and neonatal outcomes of adolescent mothers - Betina Berlitz; Carlise Dalla Rigon Nora; Rafaela Schaefer; Karin Viegas; Marilyn Agranonik; Rosangela Barbiani (Universidade Federal de Santa Maria, 2020)
Objective: to compare obstetric and neonatal outcomes among adolescent and adult mothers. Method: cross-sectional study based on data from the Sistema de Informações de Nascidos Vivos (Live Birth Information System) comparing socio-demographic, obstetric, and neonatal variables of adolescent and adult mothers from Rio Grande do Sul in the period 2010-2016. The Chi-square test evaluated statistical association and the prevalence ratio was estimated. Results: there were significant differences between mothers aged 10-14 and those from other strata: prevalence of black or brown-skinned race/color (PR=1.53; CI95% 1.46-1.60), inadequate prenatal care (PR=1.89; IC95% 1.84-1.94), prematurity (PR=1.35; CI95% 1.27-1.43), low birth weight (PR=1.34; IC95% 1.25-1.43) and lower performance in the 1st minute Apgar score (PR=5.68; IC95% 5.49-5.88). Conclusion: prevalence of risk factors for obstetric and neonatal outcomes of adolescents aged 10-14 requires careful health evaluation. Early pregnancy in adolescence requires the activation of interdisciplinary teams, and family, social assistance and socio-legal protection networks.